What should be subtracted from 2x³ - 3x²y + 2xy² + 3y³ to get x³ - 2x²y + 3xy² + 4y³
Solution:
We have to subtract a suitable term from the given expression 2x³ - 3x²y + 2xy² + 3y³. to get x³ - 2x²y + 3xy² + 4y³
Let the term to be subtracted be N.
Now, 2x³ - 3x²y + 2xy² + 3y³ - N = x³ - 2x²y + 3xy² + 4y³
On rearranging,
2x³ - 3x²y + 2xy² + 3y³ = x³ - 2x²y + 3xy² + 4y³ + N
By combining like terms,
N = 2x³ - 3x²y + 2xy² + 3y³ - (x³ - 2x²y + 3xy² + 4y³)
N = 2x³ - 3x²y + 2xy² + 3y³ - x³ + 2x²y - 3xy² - 4y³
N = 2x³ - x³ - 3x²y + 2x²y + 2xy² - 3xy² + 3y³ - 4y³
N = (2 - 1)x³ + (-3 + 2)x²y + (2 - 3)xy² + (3 - 4)y³
N = (1)x³ + (-1)x²y + (-1)xy² + (-1)y³
Therefore, N = x³ - x²y - xy² - y³
✦ Try This: What should be subtracted from -8mn + 3m² + 6n² to get 2m² + 3mn + 2n²
☛ Also Check: NCERT Solutions for Class 7 Maths Chapter 12
NCERT Exemplar Class 7 Maths Chapter 10 Problem 60 (a)
What should be subtracted from 2x³ - 3x²y + 2xy² + 3y³ to get x³ - 2x²y + 3xy² + 4y³
Summary:
x³ - x²y - xy² - y³ should be subtracted from 2x³ - 3x²y + 2xy² + 3y³ to get x³ - 2x²y + 3xy² + 4y³
☛ Related Questions:
visual curriculum